Situation Report: Hungary, 5 May 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Private Artisans on the Increase Economic Committee Calls for Support of Small and Medium-Sized Enterprises Trade Union and Youth League Leaderships Reshuffled Noted Literary Translator Advocates Closer Ties with Neighboring Countries New Benefits for Private Plots Szekszard Small Animal Breeding and Marketing Co-Operative Lack of Funds Hampers "Sow" Campaign Janos Peter's Visit to the Netherlands Recruiting Gastarbeiter for the GDR